(Work Well-Being Selama Masa Pandemi Covid-19 Ditinjau Dari Emosi Positif, Dukungan Organisasi dan Grit) - mubarak, Husni; Rostiana, Rostiana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Work Well Being is an employee condition that describes his understanding of the ability to manage his life normally, overcome pressure, work productively and contribute to his institution. This study aims to see the relationship between work well-being during the Covid-19 pandemic in terms of positive emotions, organizational support, and grit. 150 participants who were employees of a media company in Jakarta were involved in this study who were selected based on the convenience sampling method. This research is a quantitative correlational study. Data were collected using the Employee Well Being Scale from Pradhan and Hati; Shiota, Keltner, and John's Dispositional Positive Emotions Scale; The Survey of Perceived Organizational Support from Eisenberger; and the Grit-S Scale from Duckworth and Quinn. Data analysis using multiple linear regression method. The results show that (a) there is a positive and significant relationship between positive emotions and work well being during the Covid-19 pandemic, (b) there is a positive and significant relationship between organizational support and work well being during the Covid-19 pandemic, (c) ) there is no relationship between grit and work well being during the Covid-19 pandemic.